Analisis Incremental Kelayakan Penambahan Lini Perakitan Engine Motor Pt Abc - Jonny, Jonny (Bina Nusantara University, 2013)
Manufacturing motorcycle unit in Plant 1 of PT ABC requires engine supply from Plant 2. This has some burden on the operating cost of Plant 1 and the opportunity loss as well due to delay of motor engine delivery. Based on the problem, team proposes additional engine line in Plant 1 to cut engine supply from Plant 2. Therefore, team analyzes this proposal using incremental analysis to determine whether the proposal is feasible or not by comparing before and after condition with result NPV about IDR 967 Billion and Payback Period under 1 year. By this result, team determines that this proposal is recommended to be approved by management.